67. Experimental validation of algorithms used to estimate effective dose during interventional radiology procedures. (December 2018) - Negri, P.; Campi, F.; Crescenzo, S. De; Garlati, L.; Tambussi, O.
Abstract : Purpose: During interventional radiology procedures the medical staff is exposed to X-rays scattered from the patient, so it is fundamental to wear personal protective equipment. In order to evaluate the effective dose, two dosimeters shall be used: one above the protective apron and one under the protective apron. Several algorithm have been developed to combine the readings of the dosimeters, currently there is no international consensus on which is the best one. In this work, typical interventional radiology procedures have been simulated in order to experimentally verify the accuracy of the algorithms. Material and methods: Eight different irradiation conditions have been simulated in an angiographic room at Niguarda Hospital in Milano. The patient has been reproduced with two different RW3 slabs; the effective dose to personnel has been calculated by TLD inside a Rando-Alderson phantom. Personal dose equivalent (Hp(10)) have been measured by 17 dosimeters, placed on the phantom surface. The phantom has been equipped with a thyroid shield and a protective apron during two irradiations; in the other irradiations, corrections have been applied to dosimeters readings to take into account the effect of protective clothes. Results: The majority of the algorithms tend to be too conservative, only the one proposed by the NCRP tend to underestimate the effective dose: the algorithms suggested in the ICRP draft seems to be the more reliable. However there are many factors which can affect the accuracy of the algorithms, so it is impossible to achieve a great precision in the evaluation of the effective dose. Conclusions: The algorithms proposed by the ICRP draft shall be used to estimate the effective dose in interventional radiology; in case of risk to exceed the dose limit, it is better to further investigate the irradiation conditions.